2020
DOI: 10.3892/etm.2020.8512
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation ameliorates active ulcerative colitis

Abstract: Ulcerative colitis (UC) is a complex chronic pathological condition of the gut in which microbiota targeted treatment, such as fecal microbiota transplantation (FMT), has shown an encouraging effect. The aim of the present study was to investigate the efficacy and safety of FMT in patients with mild or moderate UC. A single-center, open-label study was designed, including 47 patients with mild or moderate active UC who received three treatments of fresh FMT via colonic transendoscopic enteral tubing within 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 57 publications
2
32
1
Order By: Relevance
“…The increased microbiota diversity reported by several authors in UC patients after FMT from multi-donor blended stool (2–7 donors) [ 11 , 12 , 13 , 14 , 15 ] was not found in our study using one donor for all patients. The finding reported in this work of no significant differences in Shannon diversity in FMT responders and non-responders between the baseline and any other sampling point after therapy initiation is in agreement with the studies of Damman et al [ 17 ] and Kump et.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…The increased microbiota diversity reported by several authors in UC patients after FMT from multi-donor blended stool (2–7 donors) [ 11 , 12 , 13 , 14 , 15 ] was not found in our study using one donor for all patients. The finding reported in this work of no significant differences in Shannon diversity in FMT responders and non-responders between the baseline and any other sampling point after therapy initiation is in agreement with the studies of Damman et al [ 17 ] and Kump et.…”
Section: Discussioncontrasting
confidence: 92%
“…F. prausnitzii has even been suggested to constitute a marker of a healthy gut [ 57 , 58 ]. The increased levels of F. prausnitzii after FMT found in this study have been also reported by Chen [ 14 ] and Fuentes [ 6 ], indicating a positive influence of FMT. However, we did not find any data about the effect of FMT on Blautia in UC patients in the corresponding literature.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The role of FMT in the treatment of pediatric UC is still debated, although the safety and tolerability of this clinical practice have already been assessed [ 16 , 17 , 28 ]. Recent reviews examined the current state of knowledge on FMT in IBD, and concluded that translational research on FMT is important in order to transfer its potential to real clinical management [ 15 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The success of FMT for the treatment of Clostridium difficile infection has been proven [ 8 , 9 ]. However, several articles have already reported on FMT’s potential therapeutic use in GI and GI-related diseases, including IBD [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%